A new Strategic Dialogue: Brazil-US relations in Lula's presidency (2003-2010) - Pecequilo, Cristina Soreanu [UNIFESP] (2010)
The aim of this article is to examine Brazil and the United States bilateral relations from 2003/2010 and their strategic patterns during the Presidency of Luis Inácio Lula da Silva. The goal is to understand the development of this dialogue in the 21st century and its previous background in the Post Cold War world, identifying its evolution and change due to Brazil's growing regional and global role and US relative position